2008
DOI: 10.1177/1541204008324910
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Differential Association and Social Control Theory

Abstract: This study applies differential association and social control theories to juvenile delinquency. Using a path analysis model, relationships between family, self-image, and behavior are explored. Analyses suggest that positive self-image leads to decreased delinquency, and association with delinquent peers is the greatest predictor of delinquent behavior, regardless of race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The current study is informed by previous work conducted on the influence of peers, family cohesion, and self-worth on delinquency (see Church, Tomek et al, 2012;Church, Wharton et al, 2009). These studies demonstrated the importance of peer relationships and family cohesion on the development of delinquent behavior.…”
Section: The Current Studymentioning
confidence: 99%
See 3 more Smart Citations
“…The current study is informed by previous work conducted on the influence of peers, family cohesion, and self-worth on delinquency (see Church, Tomek et al, 2012;Church, Wharton et al, 2009). These studies demonstrated the importance of peer relationships and family cohesion on the development of delinquent behavior.…”
Section: The Current Studymentioning
confidence: 99%
“…Several studies have demonstrated a connection between deviant behavior and family stability, poverty, and available resources (Church, Tomek et al, 2012;Church, Wharton, & Taylor, 2009;Farrington, Jolliffe, Loeber, Stouthamer-Loeber, & Kalb, 2001;Loeber & Farrington, 2000). Some studies have suggested that when parents provide little monitoring it is more likely that delinquent activity will progress to gang involvement (Lahey et al, 1999;Thornberry, 1998).…”
Section: Family Cohesionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, some studies found differential effects of social bonds on male and female delinquency (e.g., Church et al 2009;Dukes and Stein 2001). According to Mason and Windle (2002), the dimensions of social bond were not only gender-specific, but also varied across different types of delinquent conducts.…”
Section: Gender and Social Control Theorymentioning
confidence: 99%